2022
DOI: 10.1101/2022.12.22.521621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anillin forms linear structures and facilitates furrow ingression after septin and formin depletion

Abstract: During cytokinesis a contractile ring consisting of unbranched filamentous actin (F-actin) and myosin II filaments assembles and constricts at the cell equator. Unbranched F-actin is de novo generated by formin and without formin cleavage furrow ingression fails. In C. elegans depletion of septin restores cleavage furrow ingression in formin (CYK-1) mutants. How the cleavage furrow ingresses without a detectable unbranched F-actin ring is not known. We report, that in this setting anillin (ANI-1) is essential … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Rather, different Anillin molecules capable of interacting with either Sticky or with Rho1/septins can functionally complement one another. It has been suggested that the unstructured N-terminus of C. elegans ANI-1 might oligomerize (Lebedev et al, 2023). However, unless oligomerization requires the first five amino acids and is not required for function, our observations of Drosophila Anillin do not support this prediction, since the two co-expressed Anillin species localized independently under all conditions, including in LatA.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, different Anillin molecules capable of interacting with either Sticky or with Rho1/septins can functionally complement one another. It has been suggested that the unstructured N-terminus of C. elegans ANI-1 might oligomerize (Lebedev et al, 2023). However, unless oligomerization requires the first five amino acids and is not required for function, our observations of Drosophila Anillin do not support this prediction, since the two co-expressed Anillin species localized independently under all conditions, including in LatA.…”
Section: Discussionmentioning
confidence: 99%